3x - 3y + 9 = 0
The y-intercept is the point on the graph where it crosses the y-axis, and has coordinates of (0, b). It is also the value of y when x = 0.
To solve for the y-intercept, set x = 0:
3(0) - 3y + 9 = 0
3(0) - 3y + 9 = 0
Subtract 9 from both sides:
- 3y + 9 - 9 = 0 - 9
- 3y = -9
Divide both sides by -3 to solve for y:
-3y/-3 = -9/-3
y = 3
Therefore, the y-intercept is (0, 3).
The x-intercept is the point on the graph where it crosses the x-axis, and has coordinates of (a, 0). It is also the value of x when y = 0.
To solve for the x-intercept, set y = 0:
3x - 3(0)+ 9 = 0
3x -0 + 9 = 0
Subtract 9 from both sides:
3x + 9 - 9 = 0 - 9
3x = -9
Divide both sides by 3 to solve for x:
3x/3 = -9/3
x = -3
Therefore, the x-intercept is (-3,0).
The correct answers are:
Y-intercept = (0, 3)
X-intercept = (-3, 0)
a 10-by-10 grid means there are 100 squares and percent is out of 100 so if you have 42% then you just need to fill in 42 squares
Answer:
{x}^{4}+4{x}^{3}y+6{x}^{2}{y}^{2}+4x{y}^{3}+{y}^{4}x
4
+4x
3
y+6x
2
y
2
+4xy
3
+y
4
Step-by-step explanation:
1 Use Square of Sum: {(a+b)}^{2}={a}^{2}+2ab+{b}^{2}(a+b)
2
=a
2
+2ab+b
2
.
({x}^{2}+2xy+{y}^{2})({x}^{2}+2xy+{y}^{2})(x
2
+2xy+y
2
)(x
2
+2xy+y
2
)
2 Expand by distributing sum groups.
{x}^{2}({x}^{2}+2xy+{y}^{2})+2xy({x}^{2}+2xy+{y}^{2})+{y}^{2}({x}^{2}+2xy+{y}^{2})x
2
(x
2
+2xy+y
2
)+2xy(x
2
+2xy+y
2
)+y
2
(x
2
+2xy+y
2
)
3 Expand by distributing terms.
{x}^{4}+2{x}^{3}y+{x}^{2}{y}^{2}+2xy({x}^{2}+2xy+{y}^{2})+{y}^{2}({x}^{2}+2xy+{y}^{2})x
4
+2x
3
y+x
2
y
2
+2xy(x
2
+2xy+y
2
)+y
2
(x
2
+2xy+y
2
)
4 Expand by distributing terms.
{x}^{4}+2{x}^{3}y+{x}^{2}{y}^{2}+2{x}^{3}y+4{x}^{2}{y}^{2}+2x{y}^{3}+{y}^{2}({x}^{2}+2xy+{y}^{2})x
4
+2x
3
y+x
2
y
2
+2x
3
y+4x
2
y
2
+2xy
3
+y
2
(x
2
+2xy+y
2
)
5 Expand by distributing terms.
{x}^{4}+2{x}^{3}y+{x}^{2}{y}^{2}+2{x}^{3}y+4{x}^{2}{y}^{2}+2x{y}^{3}+{y}^{2}{x}^{2}+2{y}^{3}x+{y}^{4}x
4
+2x
3
y+x
2
y
2
+2x
3
y+4x
2
y
2
+2xy
3
+y
2
x
2
+2y
3
x+y
4
6 Collect like terms.
{x}^{4}+(2{x}^{3}y+2{x}^{3}y)+({x}^{2}{y}^{2}+4{x}^{2}{y}^{2}+{x}^{2}{y}^{2})+(2x{y}^{3}+2x{y}^{3})+{y}^{4}x
4
+(2x
3
y+2x
3
y)+(x
2
y
2
+4x
2
y
2
+x
2
y
2
)+(2xy
3
+2xy
3
)+y
4
7 Simplify.
{x}^{4}+4{x}^{3}y+6{x}^{2}{y}^{2}+4x{y}^{3}+{y}^{4}x
4
+4x
3
y+6x
2
y
2
+4xy
3
+y
4
The bar should be 8 1/24 from the each edge of the door.
We need to subtract 10 1/4 from 26 1/3 to get the fraction of the space not covered by the towel bar.
We also need to divide the difference by 2 because we placed the towel bar in the center of the door.
1st we need to convert the mixed fractions into fractions to perform subtraction.
26 1/3 = ((26*3)+1)/3 = 79/3
10 1/4 = ((10*4)+1)/4 = 41/4
Steps in Subtracting Fractions
Step 1. Make sure the denominator is the same. 3 and 4 are the denominators, they are not the same but they are factor of 12. So,
79/3 must be multiplied by 4 = 79 * 4 / 3 * 4 = 316 / 12
41/4 must be multiplied by 3 = 41 * 3 / 4 * 3 = 123 / 12
Step 2. Subtract the numerators and place them above the common denominator
316/12 - 123/12 = 316 - 123 / 12 = 193 / 12
Before we can simplify the fraction, we must divide it by two to get the measurement of each edge of the door.
Steps in dividing fractions.
Step 1. Get the reciprocal of the 2nd fraction.
1st fraction : 193 / 12
2nd fraction : 2 /1 ⇒ reciprocal 1/2
Step 2. Multiply the 1st fraction to the reciprocal of the 2nd fraction
193 / 12 * 1/2 = 193 * 1 / 12 * 2 = 193 / 24
Step 3. Simplify the fraction.
193 / 24 = 8 1/24